Wittgenstein's philosophy of mind - Vohra, Ashok (Routledge, 2014)
Philosophers since Descartes have felt themselves compelled to make a choice between mind and body. Wittgenstein's Philosophy of Mind, first published in 1986, argues that there is no genuine epistemological problem of mind, and that the widespread philosophical scepticism with regard to our knowledge of other minds is without foundation. Ashok Vohra applies Wittgenstein's method to show that the problem has arisen through a tendency to over-philosophise our simple experiences.